Enhancing Employee Performance through Organizational Culture Strengthening, Transformational Leadership, and Job Satisfaction: An Empirical Study at PT Lotus Boga Lima - Bagus Nurkholis; Nancy Yusnita; Yayan Hadiyat (Asosiasi Ahli Administrasi Indonesia, 2026)
This study aims to examine the integrated effect of organizational culture and transformational leadership on employee performance through the mediating role of job satisfaction in a labor-intensive service context. Unlike previous studies that tend to analyze these variables separately, this research develops a comprehensive structural model that simultaneously tests direct and indirect relationships within a single framework. Using a quantitative approach and Structural Equation Modeling (SEM), data were collected from 145 non-permanent employees at PT Lotus Boga Lima, Indonesia. The findings reveal that organizational culture and transformational leadership significantly influence both job satisfaction and employee performance. Job satisfaction emerges as the strongest predictor of performance and acts as a partial mediator in both relationships. The novelty of this study lies in integrating organizational culture, transformational leadership, and job satisfaction into a unified model, validating mediation mechanisms in a labor-intensive service sector, and providing empirical evidence from non-permanent employees in an emerging economy context. These findings extend existing organizational behavior literature by highlighting dual pathways direct and indirect through which organizational factors influence performance.